Processes And Procedures For Selecting Tuna Raw Materials And Handling Them In The Fish House Ppupik Program - Tangke, Umar (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Fish House Campus Intellectual Product Business Development is a service activity carried out based on the results of lecturer research on local processed products by developing and innovating with the theme Diversification of Campus-Based Local Fishery Products with Fish Bone Flour Substitution to Increase Calcium Value and Storability. In this program, the processed products produced are canned fish of dried wood tuna and tuna rica-rica. In the canned fish production process, the product goes through several stages starting from raw material preparation, processing, canning and marketing processes. The raw material preparation process starts from the selection and purchase of raw materials, transportation to the handling process during production. This initial process determines the quality of canned fish products so that the product is suitable or not suitable for consumption by consumers. Therefore, in this process, workers must have the knowledge and experience to apply the SOPs in the Fish House Quality Guidelines and SNI related to the selection, determination of types, organoleptic quality criteria to the fish handling process and the use of production equipment, water and ice in accordance with SNI. In addition, to obtain good quality fish meat in the handling process, at each stage / work process, supervision must be carried out by officers, either the head of production or quality assurance (QC).